Tyrosine phosphorylation of the herpes simplex virus type 1 regulatory protein ICP22 and a cellular protein which shares antigenic determinants with ICP22. - Blaho, J A (1997)
At least eight herpes simplex virus type 1 (HSV-1) and five HSV-2 proteins were tyrosine phosphorylated in infected cells. The first viral tyrosine phosphoprotein identified was the HSV-1 regulatory protein ICP22. Also, two novel phosphotyrosine proteins were bound by anti-ICP22 antibodies. H(R22) is a cellular protein, while the F(R10) protein is observed only in HSV-1-infected cells.